Correlating technical and tactical, and kinematic elements: An in-depth analysis of game-related metrics and running activities in sub-elite senior male rugby union players - Ungureanu, A. N.; Lupo, C.; Chiarello, F.; Brustio, P. R. (International Journal of Sports Science & Coaching, 2024)
To comprehend the complexity of rugby union performance, it is crucial to correlate technical and tactical, and kinematic elements specifically for playing roles. Hence, this study investigated the relationship between game-related metrics and running activities in sub-elite senior males. Technical and tactical performance and running activity of 36 sub-elite senior players (age mean = 25 years; total performances = 200) were assessed in relation to 17 key performance indicators (KPIs). A series of general linear mixed models were performed to evaluate the relationship between KPIs according to roles (backs, forwards and scrum halves), including subjects and games as random effect. The main finding was that the tactical context relates distinctly running activities, and this effect varies between backs and forwards. Tackling mainly involves impacts and deceleration, whereas carrying the ball is associated with impacts and accelerations. Furthermore, the percentage of missed tackles is related to higher occurrences of acceleration events. These findings offer a more profound understanding of the physiological requirements in sub-elite rugby performance, especially given the limited evidence on the interaction between technical and tactical performance and running activities in sub-elite rugby union games. As a result, coaches and physical practitioners should design and execute diverse training sessions that consider both the tactical context and the players` positions.